The return of the Kurdish question: On the situation of the Kurds in Iraq, Syria and Turkey - Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2015)
For decades, the roughly twenty-nine million Kurds living in Turkey, Iran, Iraq and Syria were regarded primarily as a threat to the territorial integrity of those states and thus to the stability of the Middle East. Today the region is marked by state collapse, rampant terrorism, and signs of unravelling in the established system of states. These developments have brought about fundamental changes in the position of the Kurds and the role they play in regional politics. (SWP Comments)
Keywords: 320